Analysis of Policy Change Relating to Presidential Regulation No.19 year 2016 on Health Insurance became Presidential Regulation No.28 year 2016 on Health Insurance - Simanjuntak, Julian; Sjaaf, Amal Chalik (Journal of Indonesian Health Policy and Administration, 2017)
The rapid change from presidential regulation no.19 year 2016 on health insurance into presidential regulation no.28 year 2016 on health insurance get a big attention. This research was purposed to analyze about health insurance policy which changed very quickly. It changed from presidential regulation no.19 year 2016 into presidential regulation no.28 year 2016 on health insurance. The researcher used qualitative methods. The analysis from the input processing and output showed that the change of presidential regulation is a responsive form from president when he looked public rejection response for the increase of fee. The president extended it through the department of health affairs. In terms of inputs, the resources of this policy change are still very limited, while at the stage of the process there is still a lack of cross-sector coordination with related institutions and difficulties in getting the materials needed in the discussion. Presidential Regulation No.28 of 2016 on Health Insurance that became the output in this change is considered to be able to accommodate the demand of the people but the changes are not in accordance with the actuary calculations. This change of presidential regulation not yet affected to appropriate the fee adequacy on BPJS Implementation. The department of health affairs as a leader of health sector was recommended to increase the cross-sectoral coordination which can manifest the better product of health policy and to complete the policy instrument that yet to be determined. It also used to be concern from the department of health affairs, DJSN and BPJS which explained the increase of fee must be offset by a quality improvement rather than the implementation of national health insurance.